Fish Market Development Strategy By The Government Of The Second Largest City In Indonesia - Eko Supeno, M. Si., Ayu Karina Putri, (Opción)
The potential marine products spur the government to improve the marketing and development of fishery facilities by establishing a Fish Center. At the initial stage of Fish Center development, the trade activity was not optimum. Nevertheless, the Government of Surabaya has continuously repaired and improved this site. As a result, this Fish Center has grown up considerably. This research aimed to elaborate on the strategy applied by the Government of Surabaya in developing the Fish Center. This research was a descriptive qualitative study which was taken place in the Surabaya Agricultural Office, Surabaya Office of Cooperatives and Micro, Small, and Medium Enterprise, as well as the Fish.